Read, reason, write : - Seyler, Dorothy U. (McGraw Hill, 2004)
This text with readings presents clear instruction in critical reading and analysis, argument, and research techniques, along with a collection of current and incisive readings appropriate for practising these techniques. It should help students develop into better writers.